Influência de parâmetros físico-químicos na formação e no decaimento de espumas - Tiuman, Erich Takenore (2021)
Foams can be found in various applications such as the food and cleansing industry, or even in oil industry applications. In the latter, knowledge of the formation and decay of these structures is very important in order to correctly size the equipment of gas/oil/water separation (three-phase). However, the formation of these foams can generate several problems such as liquid carry-over, gas carryunder, decreased capacity and difficulty in measuring level, which motivated this study. Thus, this study proposed to analyze the influence of certain physical-chemical parameters such as temperature (20-0°C), pressure (1-10 bar) and types of gases (nitrogen and methane) on column formation and stability of the foam formed in ISO14 mineral oil + Sodium Lauryl Ether Sulfate + Water. To carry out this analysis, an experimental apparatus was designed and mounted consisting of a transparent foaming cell with 0.5 m height and 5 cm internal diameter. Parameters such as foamability, foaminess and the collapse curve were also evaluated to characterize the formed foam. In addition, simplified models of foam formation and decay by gas injection were proposed, based on models already available in the literature, which were validated with the results obtained experimentally. The experimental results showed good agreement to the literature regarding the behavior of temperature (higher temperature, lower stability), pressure (higher pressure, higher stability) and type of injected gas (dependence on solubility). Furthermore, maximum errors of 26% (at height) and 11% (decay phase) were obtained for the formation and decay models, respectively.